2021
DOI: 10.37394/23207.2021.18.25
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Economic Growth: Evindence From Azerbaijan

Abstract: The impact of financial development on economic growth has always been an important issue. Especially when financial crises occur, the relationship between financial markets and financial crises and economic activities is on the agenda. The main purpose of this study is to determine the relationship between financial development and economic growth in the Azerbaijani economy. For this purpose, VECM model estimation and Granger causality analysis was performed by taking monthly data between 2005-2019. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The effect of financial development on countries’ economic growth is well-researched and documented in the literature. Evidence revealed that financial development has a positive long-run impact on the economic growth of countries (Bibi, 2022; Mammadov and Ahmadov, 2021; An et al , 2021; Samia et al , 2020; Kacho and Dahmardeh, 2017; Ang, 2008; Levine, 2005). According to these studies, a properly functioning financial system accelerates economic growth by allocating and channeling finance to various productive investments.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of financial development on countries’ economic growth is well-researched and documented in the literature. Evidence revealed that financial development has a positive long-run impact on the economic growth of countries (Bibi, 2022; Mammadov and Ahmadov, 2021; An et al , 2021; Samia et al , 2020; Kacho and Dahmardeh, 2017; Ang, 2008; Levine, 2005). According to these studies, a properly functioning financial system accelerates economic growth by allocating and channeling finance to various productive investments.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the share of expenditures on the professional development of employees in total labour costs also decreased. This trend reflects the concentration of the improvement of the determinants of human capital in Azerbaijan only on officials, which in the future may be accompanied by a decrease in the level of efficiency of the application of physical economic theory in the economic activity of the country (Mammadov, 2021).…”
Section: Source: the State Statistical Committee Of The Republic Of A...mentioning
confidence: 99%
“…These state attempts continue to this day. Various studies are devoted to studying the reaction of local enterprises to regulatory measures (Mammadli, 2022;Mammadov and Ahmadov, 2021;Seyfullayev, 2020;Seyfullayev, 2022), but the impact of the country's financial development on the manufacturing sector's growth in resource-rich countries, including Azerbaijan, has not yet been sufficiently studied. In addition, the effectiveness of financial instruments largely depends on the economy's structure, the quality of institutions, and regulation.…”
Section: Introductionmentioning
confidence: 99%